Anchoring of self-expanding metal stents using the over-the-scope clip, and a technique for subsequent removal - Mudumbi, Sandhya; Velazquez-Aviña, Jacobo; Neumann, Helmut; Kyanam Kabir Baig, K. R.; Mönkemüller, Klaus (Endoscopy, 2014)
Background and study aims: Standard clips do not consistently prevent the migration of covered self-expanding metal stents (SEMS). The aims of this study were to assess the efficacy and safety of the over-the-scope clip (OTSC) system for anchoring SEMS to the esophagus, and to evaluate a novel OTSC removal technique. Methods: This was a single-center, retrospective, cohort study of consecutive patients undergoing SEMS anchoring with OTSC. Removal of the OTSC was accomplished using an inject-and-resect technique.Results: A total of 12 patients were included. The indications for endoscopic stenting were: tracheo-esophageal fistula (n = 7), postoperative leak or fistula (n = 4), perforation (n = 1). Successful application of the OTSC system was accomplished in all patients (100 %). Stent migration during follow-up (mean 3 weeks, range 2 – 4 weeks) occurred in two patients (16.7 %). After healing of the underlying condition, the stent was removed in six patients (50.0 %). In four patients (33.3 %), the anchored stent was left indefinitely in order to treat the underlying condition. There were no complications associated with deployment of the OTSC or SEMS removal.Conclusions: Although endoscopic anchoring of fully covered SEMS with the OTSC was feasible, easy to accomplish, safe, and prevented stent migration in most cases, larger studies are needed to confirm these encouraging early findings. The inject-and-resect technique was safe and efficient for OTSC and stent removal in all cases in which it was attempted.